Written communication and transformation of traditional social consciousness - I. A. Valdman (Библиосфера, 2015)
The article is devoted to the features of written communication in traditional societies. The paper deals with the written communication in frameworks of the traditional social consciousness specifics, determining social self-regulation through sacralization of social life significant aspects. It shows that the historical transformation of traditional consciousness is a desacralization process that takes place primarily as a destruction of certain behavioral norms and forms of activity as the only conditions for the society survival and well-being. The development of written communication leads to the book phenomenon, becoming a means of social institutionalizing of meanings that opposes one part of the social normative sense to the other one, which is also, therefore, more distinguished and can be fixed in other books. Institutionalization of separate book collections within libraries facilitates the desacralizing importance of written communication.